Enhancing Students’ Conceptual Understanding of Elasticity and Hooke’s Law Through PhET-Supported Guided Inquiry Learning: A Constructivist and Cognitive Load Perspective - Antonius Suban Hali; Francisca R. H Bokilia; Vinsensius Lantik; Amiruddin Supu; Markus Simeon K. Maubuthy (Jurnal Penelitian Pendidikan IPA, 2026)
The rapid transformation of science education in the digital era calls for pedagogical innovations that promote deep conceptual understanding rather than rote memorization. This study aims to investigate the effect of integrating PhET interactive simulations into a guided inquiry learning model on students’ conceptual understanding of elasticity and Hooke’s Law. A quasi-experimental pretest–posttest control group design was employed with 55 eleventh-grade science students at SMA Frater Don Bosco Lewoleba, Indonesia. The experimental group experienced PhET-supported guided inquiry, while the control group received guided inquiry instruction with real demonstration tools. Statistical analysis revealed that students in the experimental group achieved significantly higher posttest scores than those in the control group (t(53) = 2.89, p = 0.01), with a medium-to-high effect size (Cohen’s d = 0.67). The findings suggest that PhET interactive simulations function as cognitive scaffolds by visualizing abstract physical phenomena, reducing extraneous cognitive load, and supporting conceptual reconstruction during inquiry activities. These results highlight the pedagogical value of embedding digital simulations within inquiry-based physics instruction to enhance students’ conceptual understanding and foster meaningful learning in abstract scientific domains.